2013
DOI: 10.1124/mol.113.086413
|View full text |Cite
|
Sign up to set email alerts
|

Sox9bIs Required for Epicardium Formation and Plays a Role in TCDD-Induced Heart Malformation in Zebrafish

Abstract: Activation of the transcription factor aryl hydrocarbon receptor by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) prevents the formation of the epicardium and leads to severe heart malformations in developing zebrafish (Danio rerio). The downstream genes that cause heart malformation are not known. Because TCDD causes craniofacial malformations in zebrafish by downregulating the sox9b gene, we hypothesized that cardiotoxicity might also result from sox9b downregulation. We found that sox9b is expressed in the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 44 publications
6
50
0
Order By: Relevance
“…46,47 Although it remains unknown whether sox9b downregulation occurs within testicular tissue acutely after TCDD exposure, and then has implications for testes development, sox9b upregulation may support our hypothesis that some of the transcriptomic changes may be due to long-term feedback/compensatory mechanism(s) in response to disruptions in testes homeostasis.…”
Section: Figsupporting
confidence: 72%
“…46,47 Although it remains unknown whether sox9b downregulation occurs within testicular tissue acutely after TCDD exposure, and then has implications for testes development, sox9b upregulation may support our hypothesis that some of the transcriptomic changes may be due to long-term feedback/compensatory mechanism(s) in response to disruptions in testes homeostasis.…”
Section: Figsupporting
confidence: 72%
“…To test this we made use of a newly derived reporter line Tg(−2421/+29 sox9b:EGFP ) that expresses EGFP from sox9b promoter elements (Plavicki et al, 2014; Hofsteen et al, 2013), and co-stained for collagen 2a1 to mark the chondrocytes. Consistent with previous reports that sox9b is expressed in the pharyngeal endoderm (Dalcq et al, 2012; Yan et al, 2005), we found EGFP expressed in perichondrial cells surrounding the immunostained collagen 2a1-expressing craniofacial cartilages, (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We know that TCDD repression of sox9b is a key element in producing craniofacial malformations (Xiong et al, 2008). We have recently constructed a sox9b:EGFP reporter fish, Tg(−2421/+29 sox9b :EGFP) that aids the investigation of jaw development and understanding the effects of TCDD (Plavicki et al, 2014; Hofsteen et al, 2013)…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that TCDD blocked development of the epicardium, which is crucial to heart development, through inhibition of proepicardium formation in developing zebrafish (Plavicki et al, 2013). The same studies further clarified the role of Sox9b in epicardial formation and pericardial edema using Sox9b-morphant and -null mutant, suggesting partial involvement of Sox-9b in TCDD-induced edema (Hofsteen et al, 2013). Thus, mechanisms of the circulation failure, particularly pericardial edema, caused by TCDD are only beginning to be understood in developing zebrafish as well as other fish.…”
Section: Introductionmentioning
confidence: 80%